Quality excellence in pharmaceuticals – A study of comparative dissolution profile for pantoprazole sodium EC pellets 20% w/w (pfi) - VENKATESWARA REDDY BOYA; DR. K. S. SEKHARA RAO (International Journal of Pharma and Bio Sciences, 2018)
This study was carried out to prove the Quality Excellence of Pharmaceutical Formulation Intermediate (PFI) Pantoprazole Sodium EC Pellets 20% w/w by comparing it with the reputed market reference sample (Sun Pharmaceutical Industries Ltd.). This study was taken up on antiulcer drug to cure ulcers, as majority of people are suffering from gastric ulcer worldwide. One of the antiulcer drug known as Pantoprazole is, Proton Pump Inhibitor (PPI) which decreases acid secretion from parietal cells which are present in human stomach. Both Pantoprazole Sodium EC Pellets 20% w/w and PANTOCID® samples were analysed for dissolution studies in different dissolution media i.e. 0.1N Hydrochloric acid, pH 4.5 Acetate buffer, pH 6.8 Phosphate buffer for 12 units by taking testing method from USP-40. The Comparative Dissolution Profile (CDP) of Pantoprazole Sodium EC Pellets 20% w/w sample was found to be as good as the reference sample of PANTOCID®. The f2 values were found more than 50 (76 in 0.1 N HCl, 79 in pH 4.5 Acetate buffer & 77 in pH 6.8 Phosphate buffer) in all the dissolution media with reference to dissolution guidelines of Medicines Control Council (MCC), South Africa, and hence the CDP was considered acceptable and thus the quality excellence for Pantoprazole Sodium EC Pellets 20% w/w has been achieved.